Artificial Intelligence as a Pedagogical Tool in Mathematics Courses: A Descriptive Study of Prospective Elementary School Teachers - I Gede Wahyu Suwela Antara; Komang Sujendra Diputra; Kadek Adrian Surya Indra Wirawan (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2025)
The rapid development of artificial intelligence has created new opportunities for enhancing mathematics learning, including in the preparation of prospective elementary school teachers. This study describes the use of artificial intelligence as a pedagogical tool in mathematics courses at the Primary School Teacher Education Program of Universitas Pendidikan Ganesha during the even semester of the 2024/2025 academic year. A descriptive quantitative approach was applied to 118 students enrolled in Elementary Algebra and Arithmetic, Elementary Numeracy, Measurement and Geometry, and Elementary Mathematics Teaching. Data were collected through an online questionnaire covering demographic characteristics, frequency of use, perceived usefulness, perceived ease of use, learning engagement, ethical awareness, and attitudes toward artificial intelligence. The results show high mean scores for perceived usefulness, perceived ease of use, learning engagement, and positive attitudes, while frequency of use and ethical awareness remain at moderate levels. ChatGPT emerged as the most frequently used platform, followed by Photomath, Perplexity, Gemini, QuillBot, Canva AI, and GeoGebra AI features, primarily for generating explanations, checking solutions, and designing instructional materials. These findings indicate that prospective elementary school teachers have developed favorable perceptions and a willingness to integrate artificial intelligence into mathematics learning, yet the moderate levels of usage frequency and ethical awareness highlight the need for structured training and explicit guidance to promote consistent and responsible application of artificial intelligence in mathematics education. Strengthening ethical understanding and providing systematic practice are essential to ensure that future teachers can leverage artificial intelligence effectively to improve mathematics learning in elementary schools.